Oxidative plasma chemical conversion of H[2]S in gaseous hydrocarbons atmosphere in the presence of O[2] and CO[2] - Sergey Vladimirovich Kudryashov; Andrey Yurievich Ryabov; Andrey Nikolaevich Ocheredko (Известия Томского политехнического университета: Инжиниринг георесурсов, 2016)
The relevance of the discussed issue is caused by the need to elaborate hydrogen sulfide removal methods from hydrocarbon gases for their preparation for treatment and transportation on oil or gas fields. The main aim of the study is to investigate the regularities of hydrogen sulfide removal from methane and liquid petroleum gases with oxygen and carbon dioxide additions in the barrier discharge plasma reactor with one or two high voltage electrode. The methods used in the study: gas chromatography, gas chromatography-mass spectrometry, IR-spectroscopy, elemental analysis. The main results. The authors have studied the regularities of plasma chemical conversion of hydrogen sulfide in mixtures with methane and liquid petroleum gases with O2/CO2 additions. It as ascertained that the main gaseous reaction products are hydrogen, C2+ hydrocarbons, carbon mono- and dioxide, and methanethiol (there are no methanethiol in the case of CO2), polymerous deposit is formed on electrode surface. In the case of methane the hydrogen sulfide conversion dependence on oxygen concentration is extreme. Oxygen additions to the liquid petroleum gases-H2S mixtures tend to hydrogen sulfide conversion decrease. CO2 additions to the H2S mix with both methane and liquid petroleum gases tend to increase of the hydrogen sulfide conversion. The power consumptions of H2S cleanup process of methane blends is less than the one with O2/CO2 additions. In the case of liquid petroleum gases O2 additions increase the power consumption of the process and CO2 additions decrease the power consumption of the process. The composition of a deposit which is polymerous stuff on electrode area is investigated. Line and cyclic polysulfides as well as sulfones are founded out in the deposit structure. The authors studied the kinetic regularities of plasma chemical conversion of hydrogen sulfide in mixtures with methane and liquid petroleum gases with O2/CO2 additions. A probable reaction mechanism is proposed based on the literature and experimental data as well as theoretical estimates. The mechanism consists of two composing studies. The first is initiation of hydrocarbons and H2S molecules by the barrier discharge electron with formation of hydrogen and oxygen atoms, SH and alkyl radicals. The next study is the chain reaction of radicals which was formed by the previous step to obtaining polysulfidic compounds with alkyl and oxygen end groups.